Frequency of Bacillus thuringiensis Cry1A.105 resistance alleles in field populations of the fall armyworm, Spodoptera frugiperda, in Louisiana and Florida. (May 2016) - Huang, Fangneng; Qureshi, Jawwad A.; Head, Graham P.; Price, Paula A.; Levy, Ronnie; Yang, Fei; Niu, Ying
Abstract: Fall armyworm, Spodoptera frugiperda (J.E. Smith), is a major pest of many crops and a cross-crop target of transgenic maize, cotton, and soybean containing Bacillus thuringiensis (Bt) genes. Some of the current Bt maize products for controlling lepidopteran species contain the Bt event MON 89034. The objective of this study was to determine the frequency of resistance alleles in field populations of S. frugiperda collected from Louisiana and Florida, U.S. to Cry1A.105, one of the two Bt genes in MON 89034. A total of 150 F2 two-parent families of S. frugiperda were established using single-pair mating of field-collected individuals in 2011, which included 79 families from two locations in Louisiana and 71 families from one location in Florida. F2 screen was conducted to detect resistance alleles in these families to Cry1A.105 protein in maize plants. Four out of the 79 Louisiana and 14 out of the 71 Florida families were identified to possess resistance alleles to the Cry1A.105 maize plants. Thus, the corresponding frequency of resistance alleles to Cry1A.105 maize was estimated to be 0.0158 with a 95% credibility interval (CI) of 0.0052–0.0323 for the Louisiana populations and 0.0559 with a 95% CI of 0.0319–0.0868 for the Florida populations. The resistant families survived on whole Cry1A.105 maize plants and demonstrated a significant level (>116-fold) of resistance to the Cry1A.105 protein in a diet-incorporated bioassay. These findings suggest that resistance allele frequency in S. frugiperda to single-gene Cry1A.105 maize in the U.S. southeast region apparently is not rare, most likely due to the selection of Cry1F resistance and its cross-resistance to Cry1A.105. Highlights: 150 F2 families of Spodoptera frugiperda from the U.S. southeastern region were screened for Cry1A.105 resistance. 18 families were identified to possess major resistance alleles to Cry1A.105 maize plants. The resistance allele frequency to Cry1A.105 in S. frugiperda was not rare in the region. Pyramiding Cry1F and Cry1A.105 may not be a good strategy for managing S. frugiperda.